(3GdYQGFS hGdJjLGf aj bUU GdCfHjGA aj GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s ((3Ydi Hf GdMSf Hf YHO Gddg s)
(3ChdgG (B:s
(3hGdUdGI Ydi eMeO hBdg CLeYjf , GNJHQfG GdfHi s
(3BNQgG (B:s
(3hbGdhG ge Ggd Gddg hGf Gddg YR hLd bGJd Yfge hcaGge eDfI YOhge s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1131s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs